2020
DOI: 10.1016/j.ejmp.2020.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Calculating the target exposure index using a deep convolutional neural network and a rule base

Abstract: The objective of this study is to determine the quality of chest X-ray images using a deep convolutional neural network (DCNN) and a rule base without performing any visual assessment. A method is proposed for determining the minimum diagnosable exposure index (EI) and the target exposure index (EIt). Methods: The proposed method involves transfer learning to assess the lung fields, mediastinum, and spine using GoogLeNet, which is a type of DCNN that has been trained using conventional images. Three detectors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Park et al investigated the possibility of using it as a quality control tool by using displayed EI, as per IEC standards, and also revealed that the usefulness of clinical EI, EI T , and DI, which could be recorded in DICOM header tags for monitoring the ESD based on the national diagnostic reference levels (DRLs) [ 13 , 14 ]. In clinical situations, there are several trials that have introduced the clinical EI, EI T , and DI to optimize medical radiation use [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Park et al investigated the possibility of using it as a quality control tool by using displayed EI, as per IEC standards, and also revealed that the usefulness of clinical EI, EI T , and DI, which could be recorded in DICOM header tags for monitoring the ESD based on the national diagnostic reference levels (DRLs) [ 13 , 14 ]. In clinical situations, there are several trials that have introduced the clinical EI, EI T , and DI to optimize medical radiation use [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies that make use of MIL are (Crosby et al, 2020c;Schwab et al, 2020). Other topics within the literature include model uncertainty (Ul Abideen et al, 2020;Ghesu et al, 2019), quality of the CXR (Moradi et al, 2020;McManigle et al, 2020;Moradi et al, 2019a;Takaki et al, 2020;McManigle et al, 2020) and defence against adversarial attack (Li and Zhu, 2020;Anand et al, 2020;Xue et al, 2019).…”
Section: Image-level Predictionmentioning
confidence: 99%
“…Artificial intelligence is expected to soon play a key role in diagnostic imaging [1,2], radiation therapy [3,4] and medical physics in general. It has already been demonstrated to successfully improve image quality [1], decrease radiation dosage [5,6], assign label types and identify pathology locations [7][8][9][10][11][12][13], create and optimize protocols [14], accurately segment pathology areas and organs [15,16], and optimize technology utilization [17].…”
Section: Introductionmentioning
confidence: 99%